Multidimensional compliance and outcomes in gestational diabetes - Weili Zhang; Qingqing Gong; Yan Zhu (Journal of Perinatal Medicine, 2026)
Abstract Objectives To investigate the association between a composite multidimensional compliance score and glycemic control, maternal complications, and neonatal outcomes in women with gestational diabetes mellitus (GDM), and to evaluate these associations after adjusting for potential confounders. Methods This retrospective cohort study included 360 women with GDM, diagnosed between October 2023 and January 2026 at Guiyang Second People’s Hospital. A weighted compliance score (1–3) was calculated based on blood glucose monitoring, diet, physical activity, prenatal visits, and medication adherence. Participants were grouped by compliance: high, moderate, and low. Multivariate logistic regression adjusted for age, BMI, insulin use, and mobile health app use, with multiple comparisons corrected using the Benjamini-Hochberg method. Results Most baseline demographic and clinical characteristics were comparable across compliance groups, though insulin therapy use,and mobile health application utilization differed significantly. Glycemic target achievement differed markedly: 76.23 % in the high-compliance group vs. 22.46 % in moderate and 2.00 % in low compliance. Third-trimester HbA 1c was significantly lower in the high-compliance group (5.45 % ± 0.30 %) compared with moderate (5.75 % ± 0.34 %) and low (6.04 % ± 0.46 %) group. In multivariate logistic regression, low compliance was independently associated with increased odds of macrosomia, large-for-gestational-age, preterm birth, and neonatal intensive care unit admission compared with high compliance (all p